The Role of Artificial Intelligence in Mathematics Education in Higher Education: A Literature Review - Anderha, Refiesta Ratu (IJCAR: Indonesian Journal of Classroom Action Research, 2025)
The digital transformation in higher education demands innovative, adaptive, and technology-driven learning approaches. Artificial Intelligence (AI) has emerged as a key technology with significant contributions to mathematics education at the tertiary level. This article aims to explore the role, effectiveness, and challenges of AI implementation in mathematics learning through a systematic literature review of 25 scholarly articles published between 2019 and 2024. The findings reveal that AI applications—such as adaptive learning systems, educational chatbots, predictive analytics, and AR/VR-based visualizations—enhance conceptual understanding, student engagement, and learning efficiency. However, integration of AI in mathematics education still faces several obstacles, including infrastructure limitations, educators’ readiness, and ethical concerns regarding data privacy. This review recommends strategic actions such as enhancing digital literacy for lecturers and students, investing in digital infrastructure, and developing ethical frameworks to support AI-driven learning environments. Overall, AI has the potential to transform mathematics education in higher education into a more adaptive, inclusive, and sustainable process in the digital era.